2020
DOI: 10.3390/su12176905
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Inclusive Learning and Development: A Framework towards Entrepreneurial Competency Practices for Sustainability

Abstract: This paper reviews the position of entrepreneurial competency practices for sustainability within the learning and development (L&D) narrative over the last three decades. In alignment with the United Nations’ 2030 Agenda for Sustainable Development, gaps within the context of entrepreneurial learning theories, learning delivery, and roles of interlocutors are addressed. The discourse unfolds the meaning and measurement attributes of entrepreneurial competencies, advocating for developing an inclusive fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 107 publications
2
5
0
Order By: Relevance
“…ECs have direct effect on SP; consequently, strong ECs are crucial for managers of manufacturing SMEs to connect strategic goals with long-term performance targets and achieve environmental sustainability, community welfare and public safety. This aligns with prior research conducted by Al Koliby et al (2022a), Chander et al (2020) and Kisubi et al (2022).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…ECs have direct effect on SP; consequently, strong ECs are crucial for managers of manufacturing SMEs to connect strategic goals with long-term performance targets and achieve environmental sustainability, community welfare and public safety. This aligns with prior research conducted by Al Koliby et al (2022a), Chander et al (2020) and Kisubi et al (2022).…”
Section: Discussionsupporting
confidence: 88%
“…While the literature acknowledges the importance of ECs in enhancing the sustainability of SMEs (Chander et al , 2020; Tehseen and Ramayah, 2015), prior research has produced inconclusive findings (Agyapong and Acquaah, 2016; Aquilani et al , 2017). Furthermore, the relationship between different ECs and the competitiveness of business performance is complex and warrants comprehensive examination (Al Mamun et al , 2018, 2019; Tehseen and Anderson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the better entrepreneurs apply optimal learning, are committed to learning, have an open attitude to new thinking such as new ideas, new strategies both through individual learning and looking at the market, always question what is learned and known and are willing to learn from past experiences, and have a shared vision, then entrepreneurs will be more competent in their entrepreneurship. The results of this study are also consistent with the research results of [21], and [6] which result that learning orientation has a significant effect on business performance.…”
Section: Conclusion Conclusionsupporting
confidence: 90%
“…The relationship between entrepreneurial competence and the variables contained in this study can be seen from the research conducted by [21] which results that entrepreneurial competency has a significant effect on performance and [12] results that entrepreneurial competency can mediate behavior employees in banking with their performance. In addition, research conducted by [6] revealed that in order to maximize learning about the concept of performance on resources in the company, appropriate competencies were needed.…”
Section: H2 : Learning Orientation Has Significant Effect On Business...mentioning
confidence: 99%
“…Entrepreneurial competency (EC) has been examined from various perspectives over the years. Much of the empirical work found a strong association between entrepreneurial competency practices and business performance, Chander et al [2].…”
Section: Introductionmentioning
confidence: 99%